Optimal design of wind turbines on high-altitude sites based on improved Yin-Yang pair optimization. (15th February 2020) - Song, Dongran; Liu, Junbo; Yang, Jian; Su, Mei; Wang, Yun; Yang, Xuebing; Huang, Lingxiang; Joo, Young Hoon
Abstract: This study proposes a method to minimize the cost of energy (COE) of wind turbines on high-altitude sites, in which the parameters of rotor radius, hub height and rated power are optimally designed. Firstly, the COE model is built up, and the wind turbine optimization problem is formulated. Then, Yin-Yang pair optimization is presented and improved to solve the optimization problem. Lastly, the proposed method is validated under typical wind resource distribution and different altitude scenarios. The results show that with the increase of altitude, the optimal COE increases, whereas the three optimized parameters present different trends of variation. It is indicated that by considering the influence of altitude, COE at a certain altitude can be reduced effectively. Meanwhile, the improved Yin-Yang pair optimization shows smaller iteration number of convergence and convergence time in comparison with particle swarm optimization and traditional Yin-Yang pair optimization. On this basis, sensitivity analysis of optimized parameters and optimal COE to wind resource parameters is carried out, and the influence of uncertainty of wind resource statistics on optimization results is explored. By doing that, it is shown that the rotor radius, hub height and COE are most sensitive to the change of mean wind speed, and rated power is sensitive to all three wind resource parameters. On the other hand, COE decreases with the increase of three wind resource parameters. These results can be used as a guide for the wind turbine design on the high-altitude site. Highlights: A techno-economic model considering altitude influence. A novel Yin-Yang pair optimization algorithm. Fast convergence by the improved Yin-Yang pair optimization. Main reason for increased COE with altitude rise. Sensitivity analysis of optimized parameters and COE to wind resource parameters.